Cardiac calcified amorphous tumour associated with multiple myeloma. Issue 4 (28th April 2020) - Yamanaka, Tetsuo; Fukatsu, Toru; Uchimuro, Tomoya; Takanashi, Shuichiro
Abstract : We report an 86-year-old woman who was diagnosed with multiple myeloma (MM) and was receiving chemotherapy since the age of 82. A high echoic mass attached to the mitral valve was observed on transthoracic echocardiography 4 years after the treatment. The possibility of malignancy could not be ruled out, and hence, the mass was excised surgically. Pathologically, most of the mass consisted of calcified lesion without tumour tissue, and these findings were not inconsistent with calcified amorphous tumour (CAT). This case suggests that CAT may be associated with MM and has been reported after a thorough literature review.